Wessel's tiger ornamental tarantula bite envenomation: A case report and venom analysis. (February 2023) - Alsultan, Reem; Brody, Jacqueline; Hurst, Nicholas; Welch, Sharyn; Shirazi, Mazda
Abstract: Tarantulas are commonly kept as pets and bites from some species can cause severe symptoms. Here we describe a case of a patient with transient atrial fibrillation (afib) and painful muscle cramps requiring hospitalization for pain management after being bitten by a Poecilotheria tigrinawesseli (Wessel's Tiger Ornamental) spider. He was discharged with a cardiac event monitor and outpatient cardiology follow-up. The event monitor documented transient afib which decreased in frequency then resolved halfway through the three-week monitoring period. In conclusion, tarantula envenomation is usually mild with local pain and edema most reported. However, bites by some species, such as P. tigrinawesseli may have local and more systemic, long-lasting effects. Graphical abstract: Image 1 Highlights: Poecilotheria envenomation can lead to severe muscle cramps that last for weeks. Transient atrial fibrillations can be caused by a P. tigrinawesseli bite. The protein analysis of the P. tigrinawesseli venom showed small proteins (<15 KDa).